2019
DOI: 10.1186/s12978-019-0752-3
|View full text |Cite
|
Sign up to set email alerts
|

Men’s perception of barriers to women’s use and access of skilled pregnancy care in rural Nigeria: a qualitative study

Abstract: Background Greater paternal engagement is positively associated with improved access to and utilization of maternal services. Despite evidence that male involvement increased uptake of maternal and child services, studies show that few men are participating in MNCH programs. Community leaders have long been engaged in public health promotion in rural settings and have been shown to mobilize communities to enhance changes in cultural practices related to public health. With the ultimate goal of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 46 publications
(39 reference statements)
4
32
1
Order By: Relevance
“…Our results support studies from Nigeria [ 18 , 34 , 60 , 61 ] and other African countries [ 7 , 21 , 62 , 63 ]. However, it is evident from our findings and others that these roles are often entrenched in patriarchal mores reinforced by tradition and religion [ 21 , 30 , 31 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results support studies from Nigeria [ 18 , 34 , 60 , 61 ] and other African countries [ 7 , 21 , 62 , 63 ]. However, it is evident from our findings and others that these roles are often entrenched in patriarchal mores reinforced by tradition and religion [ 21 , 30 , 31 , 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Beyond impacting on patterns of marriage, factors such as education and age impact on male partners’ health decision-making. Furthermore, patriarchal norms often entrenched in, or reinforced by tradition and religion, tend to assign men sole/overriding financier, provider and decision-making roles, and this affects access to, and utilization of maternal-child health services by women [ 1 3 , 5 , 18 , 33 , 34 ]. These demographic, traditional, religious and interpersonal relationship factors synergistically interact to influence male partners’ decisions regarding maternal-child health [ 3 , 5 , 7 , 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was drafted after a review of the literature on knowledge and attitude of men toward risk factors influencing maternal and child mortality. 6,7,9,10,20,23 (87.2%) had a positive attitude and this was statistically significant, p=0.001 (Table 5).…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 86%
“…These include gender stereotyping, lack of a definitive role for men in maternal and child health, time constraints, health facility environment and women's reservations about men's involvement. 8,9 Studies have shown that men (especially in resource poor settings) have poor knowledge on child health as well as the basic preventive measures of common causes of childhood mortality. 10,11,12 A study among men in Ekiti State showed that almost half of the respondents had a negative attitude towards childhood immunisation which is one of the major preventive measure against the common childhood killer diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this requirement, the initiative offers no guidelines to advise on potential roles for men in promoting maternal health or caring for pregnant partners. It has been suggested elsewhere that the patriarchal nature of Rwandan society leads to expectations that men make key household decisions on their own, and in some instances men’s decision-making extends into the realm of maternal care, such as by choosing where and when care will be accessed [ 29 ]. Existing research on maternal care in Rwanda has not fully explored men’s involvement in this form of care from women’s perspectives, nor considered the expectations that women have regarding the involvement of their partners during this period.…”
Section: Introductionmentioning
confidence: 99%